2014
DOI: 10.1007/s40615-014-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Daughter Dyad Recruitment and Cancer Intervention Challenges in an African American Sample

Abstract: Developing an effective youth-based health messaging intervention for African American women, who remain disparately impacted by cancer, presents unique challenges. This paper reports on the challenges with recruiting familial dyads from predominantly low-income, African American neighborhoods, as well as the challenges associated with designing and implementing an upward-directed cancer screening intervention. We developed and pilot tested an educational workshop that provided adolescents with cancer screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In much research, incentives for children (and their siblings) are usually small gifts (e.g., school supplies, toys, crafts) or, for adolescents and parents, gift cards worth a nominal amount (Ely & Coleman, 2007; Wendler et al, 2002). However, many researchers have used cash incentives with adolescents and parents (Diviak, Wahl, O’Keefe, Mermelstein, & Flay, 2006; Kogan et al, 2012; Mosavel, Ports, & Leighton-Herrmann, 2014; Nguyen et al, 2014). Free health screening for children and adolescents has been found to be an incentive for parents (Nguyen et al, 2014).…”
Section: Bronfenbrenner’s Ecological Systems Theory: a Conceptual Framentioning
confidence: 99%
See 1 more Smart Citation
“…In much research, incentives for children (and their siblings) are usually small gifts (e.g., school supplies, toys, crafts) or, for adolescents and parents, gift cards worth a nominal amount (Ely & Coleman, 2007; Wendler et al, 2002). However, many researchers have used cash incentives with adolescents and parents (Diviak, Wahl, O’Keefe, Mermelstein, & Flay, 2006; Kogan et al, 2012; Mosavel, Ports, & Leighton-Herrmann, 2014; Nguyen et al, 2014). Free health screening for children and adolescents has been found to be an incentive for parents (Nguyen et al, 2014).…”
Section: Bronfenbrenner’s Ecological Systems Theory: a Conceptual Framentioning
confidence: 99%
“…Therefore, an important consideration for parents/caregivers is a reduction in the direct cost for participation, for example, by providing transportation and child care (Brannon et al, 2013; Murry & McBride, 2004; Waheed et al, 2015). In low-income areas, some researchers have discovered that phone recruitment is not particularly successful with African American participants, due to telephone disconnections or limited cell phone minutes (Artinian, Denison, & Nordstrom, 2007; Mosavel et al, 2014; Zand et al, 2004). Others have found that email addresses and/or Facebook pages are more consistent communication avenues (Rowley & Camacho, 2015).…”
Section: Bronfenbrenner’s Ecological Systems Theory: a Conceptual Framentioning
confidence: 99%